Navigating through the changing times, a case study of Pek Sam Choon/Pek Sin Choon tea businesses in Singapore, late 1940s - 1990s - Yeo, Yi Lin (Nanyang Technological University, 2020)
The tea commerce industry in Singapore indeed had come a long way and is a good reflection of Singapore’s development and changes between the late 1940s and 1990s. As Singapore progresses through the years, she is shaped by the ongoing local and global climates which in turn influenced the types of measures and policies undertaken by the government. This had affected the tea commerce industry as the government’s ideas, which were often less favourable to tea businesses, were continually reinforced to control and reform the tea commerce industry. Nonetheless, the tea owners and merchants as well as third parties like tea-related or clan associations, business partners, and regular customers were able to constantly negotiate around the policies and measures by being self-reliant and establishing business networks which helped to shape the tea commerce industry. In the process, these tea merchants and owners also created a unique identity for themselves, one that is deeply rooted in Chinese traditions and culture yet, localised in nature with its political and economic perceptions. A case study of Pek Sam Choon and Pek Sin Choon tea businesses is utilised in the understanding and exploring of these developments and transformations.